Digital Learning Transformation Training to Improve Teachers' Pedagogical Skills at SDN Tlogowaru 01 Malang: Pelatihan Transformasi Pembelajaran Digital Untuk Peningkatan Kemampuan Pedagogik Guru Di SDN Tlogowaru 01 Malang - Adi Candra Kusuma; Dimas Rossiawan Hendra Putra; Herwandi Herwandi; Delila Cahya Permatasari; Imam Saukani; Denda Dewatama (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
Teachers' ability in pedagogical competence must be improved. Teachers must always innovate in designing the learning process where learning is the main activity in the education process. Teachers are still found to use learning that is focused not on students. A big challenge for educators, especially elementary school teachers, is to be able to provide interesting and easily understood material for students. Through these challenges, every educator is required to be more creative in delivering material and attracting the attention of students. Observing the conditions that occur at SDN Tlogowaru 1, this activity aims to provide Digital Learning Transformation Training to Improve Teachers' Pedagogical Skills at SDN Tlogowaru 01 Malang. The training participants were 22 teachers with the Participatory Action Research (PAR) Method. The results of Community Service (PPM) activities increased teachers' knowledge and skills in creating interactive teaching materials through flipbook and scratch applications. Teachers are expected to be able to implement them into their learning in their respective classes. PPM participants gave a positive response of satisfaction of 16.36% Strongly agree, 82.73% Agree